PROTECTIVE EFFECT OF GARCINIA KOLA (KOLAVIRON) EXTRACT ON PREDISPOSITION OF RATS TO CARDIOVASCULAR DISEASES FOLLOWING SEPARATE ADMINISTRATION OF AMODIAQUINE AND ARTESUNATE - Ajani, E. O.; Shallie, P. D.; Adegbesan, B. O.; Salau, B. A.; Adesanya, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
This study was carried out to investigate the cardiovascular effect of administration of antimalarial drugs amodiaquine and artesunate and the efficacy of Garcinia kola extract (kolaviron) in protecting against such possible effect. Thirty (30) adult male albino rats divided into six (6) groups were used in this study. Groups D, E and F were treated with 100 mg/Kg b. w of the extract twice daily for the first one week and 200 mg/Kg b. w. /day for the subsequent three (3) weeks. Amodiaquine (10mg/Kg. b. w. /day) was administered orally for four (4) days into rats in groups A and E while rats in groups B and F were treated with artesunate (5mg/Kg b. w. /day) for four (4) days. Group C rats (normal control) were treated with normal saline. All the rats were sacrificed after four (4) weeks treatment period. Blood was withdrawn by cardiac puncture while the liver, kidney, stomach and heart were removed, cleansed and weigh. Total cholesterol, LDL- cholesterol, HDL- cholesterol and triglycerides were measured in the serum, while total fibrinogen, platelet count, red blood cell and white blood cell count were measured in the whole blood. The artherogenic and coronary risk index were also determined. Results indicate that both amodiaquine and artesunate predispose to cardiovascular disease, however the effect was more pronounced with artesunate than amodiaquine. The result also suggests that both drugs could increase the risk of coronary and artherogenic diseases and that Garcinia kola do not prevent the cardiotoxicity and coronary risk effect.